The Birth of the Myth About the Byzantine-Bulgarian War of 863 - Bardola, Kostiantyn (Studia Ceranea, 2023)
The Byzantine-Bulgarian relationship from the mid-9th to the early 10th century has attracted the attention of historians for years. However, this topic is fraught with multiple myths and misconceptions. The Byzantine invasion of Bulgarian territories in 863 is one of these myths. This hypothesis became part of the master narrative of Bulgarian national historiography and significantly impacted the clarification of the actual motivation of all parties in the complex political process. However, an analysis of sources shows that the military raid under Basileus Michael III and Caesar Bardas into Bulgarian territory is nothing more than fiction. According to a new Byzantine propaganda policy, this narrative was created after the mid-10th century. This research observes how a simple interpolation becomes a historiographical hypothesis and the dominant historiographical narrative. Additionally, a new interpretation of the beginning of Bulgarian Christianization is proposed.